PEMILIHAN KARIR PADA PEGAWAI GENERASI MILLENIAL (STUDI KASUS : PEGAWAI PT XYZ) - FEBRU RADHIANJAYA (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
PT XYZ is a company engaged in the field of production and services that has Human Resources spread throughout Indonesia. In this study, the object of observation is the employee in the East Java Unit which has a total of 2,300 personnel with the composition of the Millennial Generation (born 1981-1994) of 51% as the dominating number of employees in PT XYZ. The results of an interest survey conducted on 698 structural employees at the Basic Supervisor level (managerial type career) at PT XYZ East Java Unit, showed that 25% or 171 employees of the millennial generation chose functional careers (type of expertise). This phenomenon is then explored further in the research objectives, namely what factors influence career selection in millennial generation employees. This research is a qualitative research that uses the interview method. The result is that there are two factors that influence career choice, namely responsibility and type of work. Keywords : Millenials, Careers, Qualitative